Ophiolit zone of Thai Nguyen - Cao Bang - Chương, Văn Đức; Thắng, Trần Văn; Tùng, Văn Đức; Linh, Phan Doãn; Việt, Lê Triều (Vietnam Journal of Earth Sciences, 2018)
Ophiolit zone of Thai Nguyen - Cao Bang started from the border of Vietnam with China, then stretched in passing Cao Bang - Dong Khe - Sac Can - to Thai Nguyen. The structure of the ophiolit zone devided into five complex : - Dunite - serpentinit - peridotite complex, - Folliation gabros complex, - Gabros - diabaz complex, · - Bazan toleit complex, - Sediment of marginal complex. The formation of Ophiolit zone occurred in the begining Permi and ending in the late of Triassis by over slip of Eurasian plate over Song Hien marginal sea.